Spectroscopy of candidate electromagnetic counterparts to gravitational wave sources. Issue Volume 12:Issue S324(2016) (23rd June 2017) - Steele, Iain A.; Copperwheat, Chris M.; Piascik, Andrzej S.
Abstract: A programme of worldwide, multi-wavelength electromagnetic follow-up of sources detected by gravitational wave detectors is in place. Following the discovery of GW150914 and GW151226, wide field imaging of their sky localisations identified a number of candidate optical counterparts which were then spectrally classified. The majority of candidates were found to be supernovae at redshift ranges similar to the GW events and were thereby ruled out as a genuine counterpart. Other candidates ruled out include AGN and Solar System objects. Given the GW sources were black hole binary mergers, the lack of an identified electromagnetic counterpart is not surprising. However the observations show that it is possible to organise and execute a campaign that can eliminate the majority of potential counterparts. Finally we note the existence of a "classification gap" with a significant fraction of candidates going unclassified.